Emotional Reactivity and Death Anxiety in Dialysis Patients - Nurcan Uzdil; Nuray Şimşek; Züleyha Kılıç (Genel Tıp Dergisi)
Aim: This study was conducted as a correlational and comparative pilot study to determine the relationship between emotional reactivity and death anxiety in dialysis patients. Method: The study was conducted with a total of 140 people, including 70 hemodialysis (HD) and 70 peritoneal dialysis (PD) patients. A questionnaire form, Turkish Death Anxiety Scale (TDAS) and Emotion Reactivity Scale (ERS) were used for data collection. Results: There was no difference between the mean ERS and TDAS scores of hemodialysis and peritoneal dialysis patients. A moderate positive correlation was found between the mean ERS and TDAS scores in HD and PD groups (p<0.05). It was determined that 15.3% of TDAS scores of hemodialysis patients and 26.2% of TDAS scores of PD patients are explained by ERS. Conclusion: It was observed that death anxiety and emotional reactivity were at a moderate level in hemodialysis and peritoneal dialysis patients and there was a similarity between dialysis modalities.